2020
DOI: 10.1111/jcmm.15329
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ATB promotes ovarian cancer tumorigenesis by mediating histone H3 lysine 27 trimethylation through binding to EZH2

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Accumulating evidence has indicated that lncRNAs determine cancer cell fate through the regulation of target gene expression via interaction with specific RNAbinding proteins, such as histone modification enzymes, transcription factors, and alternative splicer [35][36][37][38]. The splicing factor SR-rich SRSF3 displays unique RNA binding properties and is upregulated in various cancer types, including breast cancer, ovarian cancer, and gastric cancer (for review, see [39]), functioning as an oncogenic molecule in these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that lncRNAs determine cancer cell fate through the regulation of target gene expression via interaction with specific RNAbinding proteins, such as histone modification enzymes, transcription factors, and alternative splicer [35][36][37][38]. The splicing factor SR-rich SRSF3 displays unique RNA binding properties and is upregulated in various cancer types, including breast cancer, ovarian cancer, and gastric cancer (for review, see [39]), functioning as an oncogenic molecule in these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified the promotion of lnc_000231 in cervical cancer, which acts by interacting with miR ‐ 497 ‐ 5p 30 . The lncRNA ATB binds to EZH2 and downregulates the expression of DAB2IP, CDH1, LATS2, FOXC1 and CDX1, thus facilitating the progression of ovarian cancer 31 . Furthermore, our study showed that LOXL1 ‐ AS1 is highly expressed in glioma tissues and cells, and its downregulation repressed the proliferation, metastasis and VM ability of these cells.…”
Section: Discussionsupporting
confidence: 51%
“… 30 The lncRNA ATB binds to EZH2 and downregulates the expression of DAB2IP, CDH1, LATS2, FOXC1 and CDX1, thus facilitating the progression of ovarian cancer. 31 Furthermore, our study showed that LOXL1 ‐ AS1 is highly expressed in glioma tissues and cells, and its downregulation repressed the proliferation, metastasis and VM ability of these cells. These results confirmed that LOXL1‐AS1 has an aggressive role in glioma.…”
Section: Discussionmentioning
confidence: 66%
“…Increasing evidence has reported that the lncRNA ATB ( lnc-ATB ) promoted tumor progression in breast [ 99 ], prostate [ 100 ], and colon cancers [ 101 ], therefore suggesting lnc-ATB as a potential prognostic marker and therapeutic target in human cancers [ 102 ]. Chen et al have reported that levels of lnc-ATB were increased in ovarian cancer tissue and high levels of lnc-ATB were associated with poor outcomes of patients with ovarian cancer [ 103 ]. Further, the authors demonstrated that lnc-ATB directly interacts with EZH2 by RIP and RNA pull-down assays in human ovarian cancer cell lines SKOV3 and A2780.…”
Section: Non-coding Rnas Bound By Prc2 and Their Implications In Cancermentioning
confidence: 99%